Biodegradability of Poly (e-Caprolactone) Modified Wood by Decaying Fungi - Tomak, Eylem D. D.; Can, Ahmet; Ermeydan, Mahmut A. A. (Springer, 2023)
In this study, spruce wood was modified by ring-opening polymerization of e-caprolactone to graft poly (e-caprolactone) into wood cell wall by impregnation of 30%, 50%, and 70% monomer concentrations and further polymerization in DMF solution. The biodegradability of the modified wood by the wood-decaying fungi was investigated by means of weight losses, and the chemical and morphological background of the degradation process was analyzed through FTIR and SEM analysis, respectively. For this purpose, modified samples were exposed to brown rot fungi Coniophora puteana and Postia placenta, and white rot fungi Trametes versicolor and Pleurotus ostreatus attacks to determine the optimum concentration level of e-caprolactone monomer for sufficient decay resistance on media inoculated with malt-extract agar and soil, according to principles of CEN EN 113 and ASTM D 1413, respectively. A leaching test was conducted in order to evaluate any loss in effectiveness in decay resistance. Results showed that all concentrations of PCL exhibited superior decay resistance in samples after the decay test was conducted on agar media. However, modified samples gave high weight losses in soil contact decay testing. P. placenta and P. ostreatus attacks were found to be more aggressive in modified samples than other fungi attacks. 70% e-caprolactone concentration was found more efficacious in suppressing brown rot fungi attacks than lower concentrations, whilst lower concentration levels were found to be more efficacious in suppressing white rot fungi attacks than 70% concentration level. SEM and FTIR findings proved that weight losses were due to both cell wall degradations and polymer digestion by fungal enzymes. SEM study revealed that cell wall modification inhibits the consumption of cell wall polymers compared to controls.
Keywords: Biodegradability; Decaying fungi; Poly(epsilon-caprolactone) modification; Cell wall degradation; Soil contact test